2016
DOI: 10.1111/rode.12248
|View full text |Cite
|
Sign up to set email alerts
|

Credit Constraints, Technology Choice and Exports: A Firm‐level Study for Latin American Countries

Abstract: In this paper, constraints on technology choice and credit access are introduced into a firm-level trade model in a dynamic setting in order to explain factors that limit benefits to a firm from trade liberalization. Theoretical analysis shows that firms face credit constraints depending on their initial productivity and the cost of credit. As a result, credit-constrained firms may not be able to cross the minimum productivity threshold needed to enter and compete in a foreign market. Empirical analysis using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 12 publications
3
19
0
Order By: Relevance
“…Furthermore, financially constrained establishments are significantly less likely to penetrate new markets and export (Minetti and Zhu 2011), to pursue R&D activities (Mancusi and Vezzulli 2010;Mohnen et al 2008;Männasoo and Meriküll 2011;Hajivassilou andSavignac 2008 or Álvarez andCrespi 2011) to invest in capital goods (Hasan 2013) or to offer formal training programs to their employees (Popov 2013), to name but a few of their negative consequences.…”
Section: Endnotesmentioning
confidence: 99%
“…Furthermore, financially constrained establishments are significantly less likely to penetrate new markets and export (Minetti and Zhu 2011), to pursue R&D activities (Mancusi and Vezzulli 2010;Mohnen et al 2008;Männasoo and Meriküll 2011;Hajivassilou andSavignac 2008 or Álvarez andCrespi 2011) to invest in capital goods (Hasan 2013) or to offer formal training programs to their employees (Popov 2013), to name but a few of their negative consequences.…”
Section: Endnotesmentioning
confidence: 99%
“…4 See Espanol (2007), Castagnino et al (2013), Egger and Kesina (2013), Manole and Spatareanu (2010), Kiendrebeogo and Minea (2012), Ito and Terada-Hagiwara (2011), Forlani (2010), Cole et al (2010), Wang (2010). 5 Studies such as by Li and Yu (2009), Buch et al (2009), Muûls (2008), Berman and Héricourt (2010), and Hasan et al (2013) have found rather weak or limited evidence, while studies such as by Manova (2012) have shown that two thirds of the trade-specific effect of financial frictions are due to the intensive margin of trade 6 Nonparametric estimation methodology is a useful tool and widely applied in many areas of economics. The following are studies that apply nonparametric estimation techniques, among many others: Henderson and Millimet (2005) estimate the impact of environmental policy on state-level output.…”
Section: Introductionmentioning
confidence: 99%
“…5 Studies such as by Li and Yu (2009), Buch et al (2009), Muûls (2008), Berman and Héricourt (2010), and Hasan et al (2013) have found rather weak or limited evidence, while studies such as by Manova (2012) have shown that two thirds of the trade-specific effect of financial frictions are due to the intensive margin of trade…”
Section: Introductionmentioning
confidence: 99%